Magda and André Trocmé : resistance figures - Trocmé, Magda, 1901-1996; Trocmé, André, 1901-1971 (McGill-Queen's University Press, 2014)
Magda Trocmé (1901-1996) was the Italian-born wife of Reverend André Trocmé (1901-1971), a French pastor deeply involved in the social gospel movement that saw Christianity embedded in progressive political struggles. Together, they worked heroically, and under dangerous circumstances, to prevent the deportation of thousands of people to Nazi concentration camps. Living in the small, mainly Protestant town of Le Chambon-sur-Lignon on the Plateau Vivarais-Lignon in southern France, Magda and André Trocmé inspired a network of resistance to the Vichy regime's deportation of Jews and would eventually be honored as "Righteous Among the Nations" by the state of Israel. This book includes a mosaic of sermons, letters, published articles, diaries, and speeches, from the 1920s to the 1970s.